Demystifying Digital Resilience in Online Teaching: using the Technology Acceptance Model to Magnify Human Factors - Siti Noorsiah Jamaludin, Siti Noorsiah Jamaludin; Gede Pramudya Ananta, Gede Pramudya Ananta; Abd Samad Hasan Basari, Abd Samad Hasan Basari (2023)
The rapid advancement of technology in the learning environment has accelerated the digitalization of education, necessitating academicians’ embrace of digitalization in teaching and learning to meet the demand for educational activities. While it was anticipated that academicians would effectively accept the new changes, the transformation of online teaching practices spawned complexities. This study aims to comprehend the behaviour and attitude of academics toward online teaching based on a quantitative survey of 142 respondents (N = 142). The Technology Acceptance Model (TAM) is tested for gauging people’s acceptance of technology in various settings. The TAM has been expanded in this study to assess the success of actual academics in adopting online teaching practices. The previous literature review identified self-efficacy, digital anxiety, and subjective norms as human factors in online teaching. Following identifying these variables, a conceptual model with emotional aspects was designed as a new contribution to this study. Understanding academics’ digital adoption and highlighting their attitudes and behaviours regarding the acceptance of online teaching are essential goals of this research. This study is expected to provide academics with theoretical support when deciding on human factors to include in the TAM model. This study is novel in its conceptualization of the model that employs emotional aspects as an external construct to forecast academics’ acceptance of online teaching. Results show that human factors play a vital role in academics to form attitudes and behaviour toward online teaching, which may be used as a guide for implementing online teaching